2015
DOI: 10.1177/1039856214568216
|View full text |Cite
|
Sign up to set email alerts
|

Carer experience of Community Treatment Orders: implications for rights based/recovery-oriented mental health legislation

Abstract: Mental health legislation is shifting to bring a greater focus on rights, individual choice and autonomy in line with recovery-oriented care. This study describes the impact of severe mental illness and decisions in relation to CTOs on carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“… 8 , 11 However, some studies have reported preference among patients for CCT if the alternative is admission to hospital, 12 and carers also support use of CCT. 13 , 14 The benefits of CCT might also result from community services being obliged to provide care instead of any direct effect on patient behaviour. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 8 , 11 However, some studies have reported preference among patients for CCT if the alternative is admission to hospital, 12 and carers also support use of CCT. 13 , 14 The benefits of CCT might also result from community services being obliged to provide care instead of any direct effect on patient behaviour. 15 …”
Section: Introductionmentioning
confidence: 99%
“…The process of recalling people to hospital may involve emergency services, including police (19). Reform of mental health legislation in Victoria has been driven by a range of concerns including the apparent overuse of CTO, concerns about their effectiveness, and human rights issues (13). The reform also intended to promote the Act’s role in supporting recovery and improve the participation of people receiving mental health treatment and care in decision-making (13).…”
Section: Cto Use In Victoriamentioning
confidence: 99%
“…CTOs are also considered “deskilling” and forming a substitute for more innovative, well-resourced and intensive services (12). Yet, informal family supporters have tended to support the use of CTOs and have identified that these orders can assist them (13). The most recent Cochrane review of the evidence for compulsory community and involuntary outpatient treatment for people with severe mental disorders concluded that despite three randomized control trials there was still no evidence that CTOs were effective in reducing clinical outcomes such as hospital readmission and quality of life (8).…”
Section: Introductionmentioning
confidence: 99%
“…The applications of a CTO may support paternalistic practice, 25 and thus have an impact on the psychiatrist's role as a patient supporter, therefore limiting their influence on the patient. Many patients do not know that they are under a CTO, are not fully informed or do not understand the regulations of a CTO. 26 CTOs are favoured by relatives and carers, 27 possibly to force patients to comply with their wishes; this may on some occasions be in their own, but not necessarily in the patient's, best interest. The functional split between in-patient and out-patient consultants makes regulations and administration difficult. An in-patient consultant may utilise a CTO for one purpose, such as with a view to shorten an in-patient admission, without proper consultation with the psychiatrist and team who will have the task of implementing the order in the community over the longer term.…”
Section: Some Practical Points To Considermentioning
confidence: 99%
“…CTOs are favoured by relatives and carers, 27 possibly to force patients to comply with their wishes; this may on some occasions be in their own, but not necessarily in the patient's, best interest.…”
Section: Some Practical Points To Considermentioning
confidence: 99%